Pembagian Harta Bersama Pasangan Nikah Siri Yang Bercerai Dalam Pandangan Fikh Islam - Z, Zahidin; Muchtar, M.Ilham; R, Rapung (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Unregistered marriage (nikah siri), while considered valid under Islamic law if the essential requirements and pillars are fulfilled, often creates various legal and social issues in Indonesia due to the absence of official documentation. This thesis aims to analyze the rights of spouses in unregistered marriages and the provisions for the division of joint property upon divorce from the perspective of Islamic jurisprudence (fiqh). The study employs a library research approach by examining classical fiqh texts, Islamic legal literature, and relevant regulations.The findings reveal that the rights of spouses in unregistered marriages under Islamic law include maintenance (nafkah), affection, and protection. However, the implementation of these rights is often hindered by the lack of state legal recognition. Regarding the division of joint property, Islamic jurisprudence provides flexibility to resolve conflicts through reconciliation (?ul?) or justice principles based on each spouse’s contribution. Nevertheless, the absence of marriage registration places women and children in vulnerable positions, particularly in accessing legal rights such as inheritance, maintenance, and protection after divorce. This study concludes that marriage registration is essential for better legal protection, especially for women and children. It also recommends raising public awareness about the importance of marriage registration and the role of the government and religious institutions in providing legal solutions for unregistered marriages.